What is written in teacher training: an inventory on written of future teachers - Baptistella, Bruna Fabiane; Chaluh, Laura Noemi [UNESP] (Univ Federal Sergipe, 2017)
This work is a fragment of a master's degree research aimed to investigate the writing practices developed in the context of initial teacher education, specifically, on a Full Degree in Education at a public university. We bring here the writing practices inventory systematized throughout the research, which was inspired by the methodology of oral history and documentary research. When interviewing seven female students and a male student, it could be possible to identify the text genres which circulate on that context and to establish a dialogue with the data obtained from the official documents reading that revealed the practice of writing presence crossed by the research in context of initial training of that course. The data analysis from the evidentiary paradigm made it possible to think that the writing produced at initial teacher training go through three axes: the official written, marginal written and experiential written. This work brings contributions to think proposals that emphasize the writing of future teachers.
Keywords: Teacher education; Initial training; Writing practices